31 Incidental coronary artery calcification on non-cardiac computed tomography: a 5 year follow up study. (6th October 2022) - Millar, K; Giblin, G; Fitzpatrick, N; McAdam, BF
Abstract : Introduction: The presence of coronary artery calcification (CAC) on CTPA is an established risk factor for Acute Coronary Syndrome (ACS). CT angiography is highly sensitive for the detection of significant coronary artery disease (CAD). Visual ranking of CAC on low dose CT Thorax has been shown to be reliable when compared to ECG-gated calcium scoring CT scans. However, CAC that is present on CTPA is frequently underreported or indeed unreported. In 2015, we carried out a single-centre retrospective review to evaluate the incidental prevalence and burden of coronary artery calcification on CTPA used for patients presenting with chest pain suspicious for PE. This is a retrospective study of the 101 patients who were part of the 2015 study over a 5-year follow-up period. The primary endpoint was the incidence of MACE in patients who were found to have CAC compared with those without evidence of CAC on CTPA. Methods: The medical notes of all 256 consecutive patients who had CTPAs performed in our institution between 01/07/2014 to 30/09/2014 were reviewed for investigation of chest pain and dyspnoea with Wells criteria suggestive of PE. The inclusion criteria were: 1.Patients who had a CTPA during the study period. 2. Patients who were aged between 40 and 70 at the time of their CTPA being filmed. The exclusion criteria were: 1.Patients who were aged less than 40 or over 70 and 2.Patients who did not have any follow up in our institution. A cohort of 100 patients that met the inclusion criteria was identified. They were grouped into patients with evidence of CAC and without evidence of CAC (NCAC) on CTPA ( table 1 ). Results: 100 patients met our inclusion criteria. 30% were female. The median age was 57 with an interquartile range of 16.05. Patients with incidental evidence of CAC tended to be older than those with NCAC. There was no significant difference in the gender distribution between both groups. The primary outcome of 5 Year MACE occurred in 22 patients in the CAC group and only 2 patients in the NCAC group (46.81% vs. 3.77%, P=<0.001). Six patients (12.76%) in the CAC group had an ACS in the follow up period compared with 0 in the NCAC group (P=0.008). 10 patients in the CAC group underwent revascularization in the follow up-period compared with 0 in the NCAC group, with 8 (17.02%) undergoing PCI (P= 0.008) and 2 undergoing CABG (P=0.214). 28 patients (59.56%) in the CAC group attended a cardiology outpatients appointment in the follow-up period compared with fifteen (28.3%) in the NCAC group (P=0.002). 29 patients (61.7%) in the CAC group underwent coronary angiography compared with eight patients (15.09%) in the NCAC group (P=<0.001). 31 patients (65.96%) in the CAC group had a TTE in the follow-up period, compared with 36 (67.92%) in the NCAC group (P=0.017). One patient (2.13%) had a CTCA in the CAC group compared with 3 (5.66%) in the NCAC group (P=0.621). Seven patients (14.90%) in the CAC group had a CMRI, compared with 6 (11.32%) in the NCAC group (P=0.767) ( table 2 ). Conclusion: In summary, the presence of coronary artery calcification on non-gated CT pulmonary angiography is a predictor for future MACE, acute coronary syndrome and need for medical treatment and percutaneous coronary intervention. This is a significant finding and highlights the importance of reporting radiologists being alert to the presence and absence of coronary artery calcification on non-gated, non-cardiac focused thoracic imaging.